Analysis Of Clean Water And Hot Water Needs Plumbing System In The Building - Bambang Jatmika; Irpan Maulana; Ridwan Al-Faqih; Reyland Aulia Zouda; Okost Maksim Viktorovich (INTERNATIONAL JOURNAL ENGINEERING AND APPLIED TECHNOLOGY (IJEAT), 2021)
The plumbing system is an inseparable part of a multi-storey building. The plumbing system at the hotel is used to provide clean water and hot water needs. To meet the need for clean water in the design of an 8 floors building with a total of 45 inhabitants, an average number of 2,706 people per month and 100 visitors per day, a ground water tank capacity of 404.5 is required. m3 / and for the top water tank (Roof Tank) used a water reservoir of 21.59 m3. Based on the results of calculations for hot water needs where the toll of hot water needs per day is 12,900 liters including heat loss with 100% hotel occupancy and for heating time, it is obtained 9.79 hours / day using 2 units of heater heater 21.04 Kw